1978
DOI: 10.1056/nejm197812212992502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Red Cells Preserved in Protein-Poor Mediums

Abstract: Blood is normally collected into a combined anticoagulating and preserving medium. We performed a study to ascertain whether improvements could be made by separation of these two functions. Addition of saline-adenine-glucose solutions (40 to 100 ml per blood unit) to buffy-coat-poor red-cell concentrates allowed storage for as long as 35 days with 24-hour erythrocyte post-transfusion survival of 83 +/- 6.8 per cent (+/0 S.D.). Potassium leakage was lower, and in vitro hemolysis somewhat higher than that of who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…In our study, the RBC were stored in SAG with their huf fy coat. According to the data published by Högman et al [10][11][12], the effect of leuko cytes on RBC hemolysis will be the subject of further investigations. The increased stor…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the RBC were stored in SAG with their huf fy coat. According to the data published by Högman et al [10][11][12], the effect of leuko cytes on RBC hemolysis will be the subject of further investigations. The increased stor…”
Section: Discussionmentioning
confidence: 99%
“…The re maining adenine, however, is sufficient for the conservation of RBC. Högman et al [11,12] proposed a preservation medium com posed of saline, adenine and glucose (SAG): saline is the diluent, adenine prolongs the shelf life of RBC to 35 days and dextrose is a nutrient for the RBC. SAG medium is added to RBC collected with CPD after their separation from the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…SAG was later modified by the addition of mannitol (SAGM) to retard lysis (Hogman et al 1978a(Hogman et al , 1987b(Hogman et al , 1981. Hogman was the first to show that white cell enzymes contaminating red cell suspension will increase red cell lysis rates (Hogman et al 1978b) and that lysis can be reduced to manageable levels by adding mannitol to the storage solution (Hogman et al 1981).…”
Section: Current State Of Liquid Preservation At 4*cmentioning
confidence: 99%
“…At the ISBT Congress in Helsinki, July 1975, the first results were shown [1], including red cell survivals which were surprisingly favourable: 82.6% (range: 81-85%) after a 5-week storage. We continued the investigations with more careful in vitro and in vivo studies using a simple sodium chloride-adenine-glucose (SAG) storage/suspen sion medium and published the data in 1978 [2], One problem which we encountered early was the tendency of increased spontaneous storage haemolysis occurring particularly during the fourth to fifth week. However, when the whole blood units were exposed to a less vigorous spin in order to procure platelet-rich plasma, a high-quality product without increased haemolysis was obtained.…”
mentioning
confidence: 99%
“…We also found further benefits by removing the buffy coat layer before suspending the cells in the SAG solution and had indications that the removal of leuko cytes played a role in reducing haemolysis. Other inves tigators found increased haemolysis when the red cells were hard-spun and most of the plasma had been removed [2,4], but Myllylä [5] demonstrated that the haemolysis problems could be avoided (even with a hard spin) if a certain minimum volume of plasma (about 50 ml) was left with the red cells. Non-penetrating sugars Dr. Claes F. Högman At the time when improved preservation of red cells with addition of purines to the anticoagulants was put into practice in Germany and Sweden around 1965, whole blood was the dominating blood product.…”
mentioning
confidence: 99%